Integrating Agro-Cultural Tourism: A Product Diversification Model for Sibetan Tourism Village, Karangasem Regency - Ida Ayu Kintan Pradnyawati; I Putu Anom; I Made Sendra (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to develop a sustainable tourism integration model that combines unique cultural elements and agricultural practices in Sibetan Tourism Village to diversify tourism products. Building on existing research that highlights the potential of agro-cultural tourism, this research employs a qualitative approach with descriptive interpretation, utilizing interviews and observations to gather data. The findings reveal the integration of traditional Balinese ceremonies and indigenous salak farming techniques as key attractions for tourists. Moreover, the study proposes a comprehensive agro-cultural tourism model that emphasizes collaboration among stakeholders, infrastructure development, and sustainable practices. This research contributes new insights to the field of tourism studies by illustrating the importance of leveraging local cultural and agricultural resources to create a memorable and sustainable tourist experience in rural areas. The integration of these elements offers a framework for enhancing community engagement and economic viability, addressing the need for innovative tourism solutions in the region.